Cerrado e escola: os saberes tradicionais como alternativa metodológica à educação ambiental formal - Oliveira, Mirna Gertrudes Ribeiro (2007)
As a result of the Scientific Revolution which began in the 16th and 17th centuries, modernity characterizes a moment in the history of planet Earth when we human beings have managed to see ourselves separated from nature and rationally superior; therefore, devoid of essential subjective dimensions. Thus, wondering like nomadic beings blinded by the light of Cartesianism, we voraciously started to pillage natural resources which at our side should facilitate survival conditions for all generations to come. Paradoxically, in an attempt to reach high levels of material well-being, we have distanced ourselves from our essence and have ended up building an environmental society socially unjust, violent, self-centered and extremely materialistic. Consequently, a group of values that form a more sustainable and welcoming world vision have had to provide room for other essential values to implement this societal model. The 1960 s was described as being the beginning of important movements like the environmental movement. In its context, the necessity to adopt an educational demeanor which could guarantee the permanence of preservation deeds proposed by this movement came about. Then, in the 1970 s Environmental Education, as a result of various national and international discussions, gave emphasis to the formation of values in children. Our research looked for data, which could characterize Environmental Education nowadays, in two schools in Araguari, MG Brazil that focused on the first few years of primary school. Our research put us face to face with a reality that leaves no doubt: Environmental Education deviated from its objective to work with values, which emphasize concepts passed on in an attempt to increase environmental awareness is not successful, because it doesn t touch on the important dimensions in a subjective point of view. In the midst of the reality, we built a methodological proposal in Environmental Education for the educators of the primary schools based on the revival of traditional knowledge. Our proposal does not represent an attempt to rewind the film, but above all to call each educator to seek abandoned values in their own history and in the history of their people with the possibility of rethinking life of the Earth planet.